The Influence of Contextual Approach on the Mathematical Understanding and Communication Abilities as Seen from Students' Initial Mathematical Abilities - Siti Maryam Sari; Hepsi Nindiasari; Cecep Anwar Hadi Firdos Santosa (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The purpose of this research was to determine the effect of a contextual approach on students' mathematical understanding and communication abilities in terms of their initial mathematical ability (KAM) in the Pythagorean Theorem class VIII material. This research was conducted at MTs Al Ihsan Serang City in the academic year 2019-2020 even semester. Methods The research method used is a quasi-experimental, data collection techniques, namely the ability to test mathematical understanding and communication, hypothesis testing using a two-way manova with a significance level of 5%. Before testing the hypothesis, the analysis prerequisite test was carried out, namely the multivariate normality and homogeneity test, the test results were the data were normally distributed and homogeneous. From the results of the analysis test using MANOVA, it can be concluded that: there are differences in the mathematical understanding and communication abilities of students who get a contextual approach with students who get a scientific approach, there are differences in the mathematical understanding and communication abilities of students who get a contextual approach with students who get a scientific approach between high KAM and low, and there is no interaction between learning approaches and KAM on students' mathematical understanding and communication skills Keywords: Contextual Approach, understanding, mathematical communication, KAM